Novel evidence on inclusiveness of consumer access to packaged and certified rice in South and Southeast Asia - CGIAR Research Program on Rice (2021)
The evidence provides a proof of concept for policy makers to develop inclusive policies for the modernization of rice retail markets. It is relevant for rice retail markets in Southeast and South Asia as well as sub-Saharan Africa.